Media Pembelajaran Inovatif Game Based Learning Pointer pada Materi Topologi Jaringan Komputer - Setiawan, Heri; Gumilar, Nugraha; Basuki R, Zaky; Rahmawati, Diana; Agustien, Rena (Jurnal FORTECH, 2022)
The aim of this research is to design a game-based learning method for computer network courses. This method is used to increase the Army Polytechnic non-commissioned officers understanding on network topology topic. This game is called POINTER, contains an innovative game-based learning method that has adopted rules from the monopoly game. This game-based innovative learning method has been tested on student non-commissioned officers who are taking computer network courses. Educational games are one of the learning tools that can make students interested in learning and help understand lecture material. Besides studying, student non-commissioned officers play. The research method used is research and development (research and development), that aim to develop interactive learning multimedia based on educational games with instructional games models on network topology material, computer network courses. By using this learning method, student non-commissioned officers understand more about computer network topology because learning is more interesting.